EPIDERMODYSPLASIA VERRUCIFORMIS: SUATU KASUS JARANG (Media Dermato Venereologica Indonesiana, 2020)
Epidermodysplasia verruciformis (EV) is a rare genodermatosis characterized by increased susceptibility to β-human papilloma virus (HPV) infection, especially HPV type -5 and -8 and risk of malignant transformation. This condition can be inherited in an autosomal recessive manner, as well as an acquired condition. Skin lesions develop early in childhood, presenting as flat warts, seborrheic keratosis-like, or pityriasis versicolor-like.This report described a 58 year-old man with history of warts since childhood. There was no history of parental consanguinity and immunosuppression. Skin lesions are persistent and progressive, manifests as multiple hyperpigmented plaques resembling seborrheic keratosis, some of them has verrucous surfaces and hypopigmented. Histopathology examination showed hyperkeratosis and coilocyte. Treatement consists of topical retinoic acid and sun avoidance. Diagnosis of EV can be made easily based on the history, physical examination and skin biopsy. HPV serotype testing can help determine the associated EV-HPV type. Several therapeutic modalities have been tried including topical and systemic retinoids, interferon, immunotherapy, electrodesication, cryotherapy and surgery. However, definitive therapy is not yet available. Early diagnosis, patient education, protection against sunlight and regular monitoring for malignant transformation are important to improve patient’s quality of life.